Job losses, outsourcing and relocation: empirical evidence using microdata - Manuel Artís; Raúl Ramos; Jordi Suri\~nach (Institute for the Study of Labor (IZA), 2007)
Using microdata, we analyse the determinants of firm relocation and outsourcing decisions and their effects on firms' employment decisions. The results for a sample of 32 countries show that both strategies have been more intense in the EU-15 countries than in the rest and that, in some cases, they have been complementary. Regarding the determinants, we have found that while some characteristics such as size, age, activity sector, main market or belonging to a group affect both decisions, other such as a higher innovation, demand sensitivity or productivity explain why some firms choose to subcontract instead of relocate.
Keywords: 330; Industrieverlagerung; Outsourcing; Auslandsproduktion; Arbeitsnachfrage; Beschäftigungseffekt; EU-Staaten